Nothing stopped Sophie the story of unshakable mathematician Sophie Germain - Bardoe, Cheryl 1971- (Little, Brown and Company, 2018)
A biography of Sophie Germain, who grew up during the French Revolution and followed her dream of studying mathematics, becoming the first woman to win a grand prize from the Royal Academy of Sciences and changing the world with her discoveries....